Integration of Motor Vehicle Testing Service System with BLUE Smart Card - Ni Nyoman Harini Puspita (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2022)
The integration of the Motor Vehicle Testing Service System in the regions with the application of the Electronic Test Pass (Bukti Lulus Uji elektronik /BLUe) from the Ministry of Transportation is carried out to improve the quality of motor vehicle testing services. The purpose of this application is to support real-time reporting of motor vehicle testing carried out by the Regions to the Center. This application is made partial, it only accepts test result data without an operational system for the testing process, because of that, motor vehicle testing application that is integrated with the application must be provided. This study aims to build a vehicle testing system that can manage test results automatically and is integrated with BLue. The results of this study are based on the implementation process for three months, the real-time integrated testing service system runs well, which is 94,4 %. the factors that affect the value of 5,6% are influenced by the existing infrastructure and manual payment processes. The calculation of the success of this implementation is determined based on the service target which previously reached 60 minutes per vehicle to 30 minutes, the efficiency of using paper is 66,6%.